Switching from Rasagiline to Safinamide as an Add-On Therapy Regimen in Patients with Levodopa: A Literature Review - Pilar Sanchez Alonso; Beatriz De La Casa-Fages; Araceli Alonso-Cánovas; Juan Carlos Martínez-Castrillo (Brain Sciences, 2023)
Parkinson’s disease (PD) is a complex disease, and the treatment is focused on the patient’s clinical symptoms. Levodopa continues to be the most effective drug for symptomatic PD treatment. However, chronic levodopa treatment is associated with the development of motor complications in most patients. Add-on therapeutic drugs, such as dopamine agonists and monoamine oxidase B (MAO-B) inhibitors, for example, safinamide and rasagiline, may be a desirable addition to continuously increase the levodopa dose for the optimization of motor control in PD. The scientific literature shows that safinamide significantly alleviated motor fluctuations with no increase in troublesome dyskinesia, thanks to its unique double mechanism, providing further benefits to fluctuating PD patients when compared to a placebo or other drugs. Switching from rasagiline to safinamide has been shown to improve the wearing-off phenomena, which is defined as the recurrent, predictable worsening of symptoms of parkinsonism at the end of the levodopa dose until the next dose reaches a clinical effect. In this situation, safinamide may be helpful for reducing the total daily dose of levodopa, improving the OFF time and ON time without troublesome dyskinesias, and being more effective than other MAO-B inhibitors. In this narrative review, we explore the switch from rasagiline to safinamide in patients with motor complications as a feasible and effective alternative to optimize antiparkinsonian treatment.